Perencanaan Teknis dan Estimasi Biaya Preservasi Jalan Daerah Menggunakan Metode Kuantitatif serta Rekapitulasi Total RAB - Ely Mulyati; Sabrina Aurelia Rianti (Jurnal Konstruksi, 2025)
Road preservation is important to maintain functionality and support community mobility. This study analyzes the technical planning and cost estimation processes in regional road preservation work to ensure budget efficiency and implementation effectiveness. The methods include road condition surveys, damage identification, technical method selection, and plan and cost estimation preparation based on unit price analysis. The results show that proper planning greatly affects the accuracy of cost estimates and the success of implementation. The total cost estimate reached Rp 222,520,104, covering all work items. These findings emphasize the importance of data-based planning to improve the quality, service life, and sustainability of road infrastructure and support optimal and sustainable community mobility.